The Impact of Complaint Handling on Customers' Attitudes and Behavior Towards Brands/Some Multi-Industry Evidence - Gousios Christos (2009)
Research Certification, Abstact, Acknowledgements, Introduction, Background, Research Aim and Objectives, Literature Review, Customer Behavior, Customer Loyalty, Complaint Handling, Methodology, Methodological Philosophy and Approach, Data Collection, Access and Ethical Considerations, Results and Analysis, Descriptive Statistics, Hypothesis Testing, Conclusions and Research Limitations, Conclusions, Research Limitations, References, Bibliography.